The Relationship between the Creativity Levels of Music Pre-service Teachers and the Preferences of a Teacher Model Supporting Creativity - (:unkn) unknown (EXPERT PROJECTS PUBLISHING, 2021)
In this study, the relationship between the creativity levels of music pre-service teachers and their teacher model preferences that support creativity were investigated. The research was conducted with correlation model, which is one of the quantitative research methods. A total of 110 fourth grade students studying in the Department of Music in three different universities in the 2017-2018 academic year participated to the study. In the study, 'Kaufman Creativity Areas Scale Turkish Form (KCAS-TF)' and 'Teacher Index Supporting Creativity (TISC)' were used as data collection tools. It has been determined that there are positive correlations between the scores of the music pre-service teachers obtained from the KCAS-TF and the CFTIS scales, but the presence of this relationship in some subcomponents could not be confirmed. In the study, it was observed that the candidates who willingly chose the department of music teaching had higher scores from the evaluation sub-dimension of the (TISC). According to the results of the (KCAS-TF), it was concluded that the scores of the teacher candidates who do not want to teach after graduation from the artistic performance and creativity sub-dimension were lower than those who wanted to teach music.
Keywords: Kaufman Creativity Scale; music education; Creative Teacher Model; creativity in education; artistic creativity; students; relationship